Peru : Impact of the Rural Roads Program on Democracy and Citizenship in Rural Areas - Remy Simatovia, María Isabel (Washington, DC, 2012)
The rural roads program, overseen by Provias Descentralizado (subdivision of Peru's Ministry of Transportation and Communications), began in 1995, and has received funds from the Peruvian Government, the World Bank and the Inter-American Development Bank. It is a national program for the rehabilitation and maintenance of roads that link rural communities and villages with secondary and principal roads, and through these, with towns and cities of the interior, thus expanding Peru's road network to the rural village level, especially in regions with greater levels of poverty. In its twelve years of existence, the program has been evaluated several times in terms of its impact on the economy (income levels, market dynamics), on gender equity, on the culture of the high Andes, on access to basic roads, and on rural living conditions (access to education, health, etc.). However, no effort had been made to systematically understand its impacts on democracy and the quality of citizenship exercised in rural areas. The study that is presented here, commissioned by the World Bank in February 2007, has sought to analyze PCR's impacts, using two general hypotheses that make it possible to explore the relationships between public roads and democracy. The first suggests that road integration, particularly the rehabilitation and maintenance of roads that link rural villages with district or provincial capitals, decreases the costs of democratic participation. In a context of increasing participatory supply, due to the ongoing recurrence of national and municipal electoral processes, as well as to the creation of new rights of participation, new roads allow rural residents to take part in democratic decision making processes without having to incur significantly higher costs than those of residents of urban centers. The second hypothesis is more specific to the Peru Rural Roads Program (PCR, for its Spanish acronym); it suggests that the way in which the program operates, its institutional arrangements and the institutions to which it provides its services, strengthens democracy, and local civil society, strengthens new leaders, improves local management skills, and aids in political inclusion, particularly that of more vulnerable sectors.